PENGARUH BIAYA PROMOSI TERHADAP VOLUME PENJUALAN PRODUK PADA PERUM PEGADAIAN CABANG PALEMBANG - Mulyati, Sri (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The title of this research is the effect of promotional cost to sales volume at Perum Pegadaian Cabang Palembang. It is located at Jalan Merdeka Number 11 Palembang. The purpose of this research are, (1) To know the effect promotional cost to sales volume, (2) To know the most effected of sales volume in promotional variable. Data obtained through interviews. Data were analyzed through pearson correlation coefficient formula and regression coefficient. Based on the results of this analysis, the writer found that Perum Pegadaian Cabang Palembang has not been able to achieve sales targets due to mortgage products are no longer monopolized by the company. In other words, there are some mortgage products which are also owned by financial institutions or other companies, that is the service delivery money through western union. Writer concludes that the most effect of promotional cost is sales volume. The publicity variable is an excellent variable. Writer suggests that the company should increase their personal selling becouse it can improve their sales volume. Keywords— promotion cost, sales volume, publicity